Correlation between neonatal outcomes of twins depends on the outcome: secondary analysis of twelve randomised controlled trials. (25th June 2018) - Yelland, LN; Schuit, E; Zamora, J; Middleton, PF; Lim, AC; Nassar, AH; Rode, L; Serra, V; Thom, EA; Vayssière, C; Mol, BWJ; Gates, S
Abstract : Objective: To estimate the magnitude of the correlation between neonatal outcomes of twins and demonstrate how this information can be used in the design of randomised controlled trials (RCTs) in women with twin pregnancies. Design: Secondary analysis of data from 12 RCTs. Setting: Obstetric care in multiple countries, 2004–2012. Population or sample: 4504 twin pairs born to women who participated in RCTs to assess treatments given during pregnancy. Methods: Intraclass correlation coefficients (ICCs) were estimated using log‐binomial and linear models. Main outcome measures: Perinatal death, respiratory distress syndrome, bronchopulmonary dysplasia, intraventricular haemorrhage, necrotising enterocolitis, sepsis, neonatal intensive care unit admission, birthweight, low birthweight and two composite measures of adverse neonatal outcome. Results: ICCs for the composite measures of adverse neonatal outcome were all above 0.5, indicating moderate to strong correlation between adverse outcomes of twins. For individual neonatal outcomes, median ICCs across trials ranged from 0.13 to 0.79 depending on the outcome. An example illustrates how ICCs can be used in sample size calculations for RCTs in women with twin pregnancies. Conclusions: The correlation between neonatal outcomes of twins varies considerably between outcomes and may be lower than expected. Our ICC estimates can be used for designing and analysing RCTs that recruit women with twin pregnancies and for performing meta‐analyses that include such RCTs. Researchers are encouraged to report ICCs for neonatal outcomes in twins in their own RCTs. Tweetable abstract: Correlation between neonatal outcomes of twins depends on the outcome and may be lower than expected. Tweetable abstract: Correlation between neonatal outcomes of twins depends on the outcome and may be lower than expected.